Intracranial space-occupying lesion (cerebellar mass): A case report - Shil, Rahul; Mitri, Adelarisa (Indian Journal of Case Reports, 2024)
Regardless of their unclear etiology, intracranial space-occupying lesions (ICSOL) are no longer uncommon. Malignancy or any other underlying pathology could be the cause of ISCOL. According to the report, the incidence could be found in children’s as low as under the age of five. We present a case of ICSOL in a 13-year-old female. Following the magnetic resonance imaging, the surgery was done, and the prognosis was better. However, accurate and timely diagnosis is important to counsel the patient and with a better prognosis.